Governance of Assisted Living in Long-Term Care: A Systematic Literature Review - Luting Poh (MDPI AG, 2021)
Assisted living (AL) is an emerging model of care in countries where long-term care needs are escalating, with emphasis given to promoting independence and autonomy among the residents to achieve active and healthy ageing. Unlike established nursing homes, the governance of AL is nebulous due to its novelty and diverse nature of operations in many jurisdictions. A comprehensive understanding of how AL is governed globally is important to inform regulatory policies as the adoption of AL increases. A systematic literature review was undertaken to understand the different levels of regulations that need to be instituted to govern AL effectively. A total of 65 studies, conducted between 1990 to 2020, identified from three major databases (PubMed, Medline, and Scopus), were included. Using a thematic synthesis analytical approach, we identified macro-level regulations (operational authorisation, care quality assessment and infrastructural requirements), meso-level regulations (operational management, staff management and distribution, service provision and care monitoring, and crisis management), and micro-level regulations (clear criteria for resident admission and staff hiring) that are important in the governance of AL. Large-scale adoption of AL without compromising the quality, equity and affordability would require clear provisions of micro-, meso- and macro-level regulations.